2022
DOI: 10.1172/jci149371
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake exerts dual genome-wide effects on hippocampal metabolism and learning-dependent transcription

Abstract: Caffeine is the most widely consumed psychoactive substance in the world. Strikingly, the molecular pathways engaged by its regular consumption remain unclear. We herein addressed the mechanisms associated with habitual (chronic) caffeine consumption in the mouse hippocampus using untargeted orthogonal omics techniques. Our results revealed that chronic caffeine exerts concerted pleiotropic effects in the hippocampus at the epigenomic, proteomic, and metabolomic levels. Caffeine lowered metabolism-related proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…In cortical neurons BDNF is usually regarded as neuroprotective [ 82 , 83 ]. Our results may therefore suggest that the negative influence of caffeine in the ALS mouse model results from a gain of BDNF toxic function in the spinal cord together with a loss of BDNF neuroprotective function in the cortex, which cannot be compensated and may even be exacerbated by the caffeine-induced upregulation of A 1 R. The influence of chronic caffeine should not be regarded as solely related to alterations in adenosine receptors or BDNF levels, since chronic caffeine exerts a multitude of effects at the epigenomic, proteomic, and metabolomic levels, as recently shown in a comprehensive and detailed study [ 84 ]. Nevertheless, besides the involvement of BDNF and adenosine, our data tends to exclude VEGF and VEGF receptors among the chronic caffeine-induced changes in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…In cortical neurons BDNF is usually regarded as neuroprotective [ 82 , 83 ]. Our results may therefore suggest that the negative influence of caffeine in the ALS mouse model results from a gain of BDNF toxic function in the spinal cord together with a loss of BDNF neuroprotective function in the cortex, which cannot be compensated and may even be exacerbated by the caffeine-induced upregulation of A 1 R. The influence of chronic caffeine should not be regarded as solely related to alterations in adenosine receptors or BDNF levels, since chronic caffeine exerts a multitude of effects at the epigenomic, proteomic, and metabolomic levels, as recently shown in a comprehensive and detailed study [ 84 ]. Nevertheless, besides the involvement of BDNF and adenosine, our data tends to exclude VEGF and VEGF receptors among the chronic caffeine-induced changes in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Since omic studies identified adaptive changes of primary metabolism upon regular intake of caffeine [41], we next enquired if the regular intake of a moderate dose of caffeine would affect the metabolic properties of cortical synapses that are a major determinant of synaptic function and resilience under noxious conditions [55,56]. The study was carried out in synaptosomes from the mouse cerebral cortex, which is the largest brain region to provide sufficient material to complete the study.…”
Section: Impact Of Caffeine Intake On Metabolic Features Of Cortical ...mentioning
confidence: 99%
“…Importantly, the neuroprotective effects of caffeine require its prolonged intake whereas the acute administration of caffeine to naïve animals often has effects opposite to these afforded by a continuous intake of caffeine (reviewed in [29,30]): the acute administration of caffeine aggravates convulsions through inhibitory A1R [31,32], as well as brain traumatic or ischemic damage [12,33,34]; in contrast, a regular exposure to caffeine has a neuroprotective effect through the attenuation of facilitatory A2AR signalling [9,15,27,35]. Thus, it appears that repeated exposure to caffeine might induce a form of brain preconditioning, with reported alterations of brain functional connectivity [36][37][38], brain metabolism (e.g., [18,[39][40][41]) and levels of adenosine [42], as well as of A1R and A2AR in the adult brain (e.g., [43,44]).…”
Section: Introductionmentioning
confidence: 99%
“…Coffee and tea are the most popularly consumed beverages worldwide, thus, any biological effects from coffee and tea consumption could have a significant influence on public health [ 3 ]. It has been reported that coffee reduces the risks of multiple cancers [ 4 ], cardiovascular disease [ 5 ], diabetes [ 6 ], stroke [ 7 ], Parkinson’s disease [ 8 ], and gallstones [ 9 ].…”
Section: Introductionmentioning
confidence: 99%